Translation Between Unrelated Languages and Cultures, as Illustrated by Japanese-English Translation - Wakabayashi, Judy (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1991)
ABSTRACT Most writing on translation is based on Indo-European languages, which are not only linguistically related but also share a similar cultural background. In an attempt to counter this eurocentric bias, we shall discuss some aspects of Japanese-English translation, focussing especially on differences in paragraph and discourse structure and on cultural factors. The aim is to demonstrate that linguistic typology and sociocultural distance need to be taken into account in translation theory and practice. We conclude that in order to avoid misunderstanding, at times the translator of unrelated languages used in different communicative frameworks may have to step beyond what is normally regarded as the role of the translator into a role approaching that of an editor. Translation between ethnolinguistically divergent systems may contribute to translation studies by highlighting problem areas that are less evident elsewhere.